2016
DOI: 10.15420/cfr.2016:21:1
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Patients with Heart Failure: Is Enough Being Done?

Abstract: Depression is a major issue in heart failure (HF). Depression is present in about one in five HF patients, with about 48 % of these individuals having significant depression. There is a wide variation in reported prevalences because of differences in the cohorts studied and methodologies. There are shared pathophysiological mechanisms between HF and depression. The adverse effects of depression on the outcomes in HF include reduced quality of life, reduced healthcare use, rehospitalisation and increased mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 56 publications
7
50
0
1
Order By: Relevance
“…Moreover, the HDRS questionnaire was found to be the most sensitive tool for testing the depressive symptoms among patients with vitiligo. Previous studies had demonstrated that depression was a frequent comorbidity in patients with chronic diseases such as diabetes, 27 Parkinson's disease 28 and heart failure 29 . Vitiligo is the most common depigmenting disorder and up to now there are no effective or satisfactory treatments for the illness.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the HDRS questionnaire was found to be the most sensitive tool for testing the depressive symptoms among patients with vitiligo. Previous studies had demonstrated that depression was a frequent comorbidity in patients with chronic diseases such as diabetes, 27 Parkinson's disease 28 and heart failure 29 . Vitiligo is the most common depigmenting disorder and up to now there are no effective or satisfactory treatments for the illness.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of natriuretic peptides are elevated in congestive heart failure. One study reported these have an antagonistic effect on blood pressure and fluid neurotransmitters in HF and are associated with the emotional and mental changes seen in HF [39]. Further investigating this concept, Herrmann-Lingen, et al, (2003) reported that anxiety tends to reduction with high atrial natriuretic pro-Peptide levels [40].…”
Section: The Link Between Heart Failure Depression and Anxietymentioning
confidence: 99%
“…The vast majority of cardiovascular disease-related deaths (85%) can be attributed to stroke and heart failure (HF) with their accompanying detrimental effects on the human body, albeit there might be substantial geographic differences in survivability rates (1). A growing body of clinical studies suggests a high degree of comorbidity between cardiovascular diseases and cognitive impairments and emotional distress (2)(3)(4). In fact, 20-40% of all HF patients develop major depression and display anxiety levels signi cantly higher than the healthy population (2,3,5,6), which usually appear later than the cardiovascular and autonomic-related symptoms (7).…”
Section: Introductionmentioning
confidence: 99%